2022
DOI: 10.1136/flgastro-2022-102184
|View full text |Cite
|
Sign up to set email alerts
|

Ear, nose and throat (ENT) manifestations and complications of reflux

Abstract: Laryngopharyngeal reflux disease describes the backflow of acidic stomach content towards the larynx and is associated with symptoms such as cough, throat clearing and globus. It is a common presentation in primary care and the sequelae of symptoms that arise from the disease often present in ear, nose and throat clinics. Assessment and examination of patients presenting with reflux symptoms includes questionnaires, as well as direct visualisation of the pharynx and larynx, and takes a multidisciplinary team a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The results of our study showed that gastroesophageal reflux has an effect on the mucosal layer of the nasal cavity and nasopharynx that is similar in nature to the effect of laryngopharyngeal reflux on the larynx and pharynx: edema, presence of mucus, increased vascular pattern with hyperemia and hypertrophy. Many studies have highlighted the etiopathogenetic role of gastroesophageal reflux in the development of sinus and nasopharyngeal inflammation [11][12][13][14]. Analysis of the causal relationship between GERD and chronic rhinosinusitis at the genetic level has shown that gastroesophageal reflux disease increases the risk of developing chronic rhinosinusitis by 36% [15].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study showed that gastroesophageal reflux has an effect on the mucosal layer of the nasal cavity and nasopharynx that is similar in nature to the effect of laryngopharyngeal reflux on the larynx and pharynx: edema, presence of mucus, increased vascular pattern with hyperemia and hypertrophy. Many studies have highlighted the etiopathogenetic role of gastroesophageal reflux in the development of sinus and nasopharyngeal inflammation [11][12][13][14]. Analysis of the causal relationship between GERD and chronic rhinosinusitis at the genetic level has shown that gastroesophageal reflux disease increases the risk of developing chronic rhinosinusitis by 36% [15].…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 Different materials and techniques have been developed for tympanoplasty. 6 , 7 , 8 The two main methods commonly used are overlay and underlay. 4 …”
Section: Introductionmentioning
confidence: 99%
“…for tympanoplasty. [6][7][8] The two main methods commonly used are overlay and underlay. 4 The underlay method is commonly used due to its relatively easy procedure.…”
mentioning
confidence: 99%